Upaya Meningkatan Hasil Belajar Siswa Kelas II Tema 2 Subtema 2 Bermain di Lingkungan Sekolah Melalui Model Pembelajaran Problem Based Learning (PBL) SD Negeri Waru 03 - Nurwantinah, Nurwantinah (Universitas Sebelas Maret, 2020)
The background of this research is because of the difficulties experienced by the second grade students of SD Negeri Waru 03, Bantarkawung District, Brebes. It is proven by the percentage of student learning in the previous class of 30% of students who have completed. The reason is that they feel bored with the monotonous learning process and do not use varied learning methods.The model in this study uses the Problem Based Learning (PBL) model which consists of 4 stages, namely; planning, implementing actions, observing and reflecting. The subjects of this study were second grade students of SD Negeri Waru 03 Bantarkawung District, Brebes Regency for the 2020-2021 academic year with a total of 13 students, consisting of 10 male students and 3 female students. Data collection techniques using interviews, observation, documentation, and written test assessment. The results of this study can be explained as follows: 1) in the application of the Problem Based Learning (PBL) method there is an increase in teacher and student activity in each cycle, this can be proven for teacher activity in the first cycle to reach a percentage of 80% (good), while in the second cycle teacher activity reached a percentage of 100% (very good). Student activity in the first cycle reached a percentage of 69.16% (good), while in the second cycle it reached a percentage of 90.00% (very good) so that in the second cycle it was declared successful because it had reached the KKM